EDUKASI PEMANFAATAN LIMBAH KOTORAN TERNAK BERBASIS ZERO WASTE PADA USAHA PETERNAKAN SAPI POTONG DI DESA TULABOLO BARAT - Siti Aisyah R; Yanti Saleh; Mohammad Zubair Hippy (Jurnal Abdi Insani, 2023)
One potential area for development in the livestock subsector is beef cattle, including waste processing, which can provide income and contribute to improving community welfare. Waste originating from cow dung contains chemicals including NH3, NH, and other compounds. The people of West Tulabolo Village do not optimize the use of cow dung because they have a limited understanding of the negative impacts of environmental pollution caused by cow dung. The main objective of PKM activities is to increase farmers' understanding of waste management practices on zero-waste-based beef cattle farms. The various stages carried out in this PKM activity include observation, counseling, training, and evaluation. The target audience for this PKM partner is the wider community, with a special focus on farmers and beef cattle breeders in West Tulabolo Village. The participants were given an educational introduction to processing waste produced by beef cattle based on zero waste. In the context of this PKM activity, some of the learning material was disseminated theoretically so that it could provide additional knowledge for the community, and training activities in making organic fertilizer were continued. The participants showed high enthusiasm for participating in the training session. The participants had increased knowledge and skills related to management in the use of beef cattle manure waste. Analysis of the pre-test and post-test results shows that the counseling and training provided to the target audience has provided good results in terms of the application and utilization of zero waste-based livestock waste in the realm of science and technology as well as contributing to the rural economy.